A Model for Security Evaluation of Digital Libraries: A Case Study on a Cybersecurity Curriculum Library (Journal of The Colloquium for Information Systems Security Education, 2020)
The use of digital libraries (DLs) is increasing. To attract users and sustain digital libraries, security of these systems is critical. However, few studies in the digital library literature have focus on evaluating the security of a DL system. Through review of existing literature, standards and other security guidelines, we propose a novel model for security evaluation of digital libraries. We test the effectiveness of the model using the CLARK cybersecurity curriculum digital library (www.clark.center) at Towson University. We identify five core security criteria that are broken down into several requirements, in the model, that a DL should fulfill to achieve security. Results from the evaluation, which include static code analysis and expert review of CLARK’s security mechanisms, indicate the proposed model is significantly effective in evaluating the security requirements of digital libraries.
Keywords: digital libraries; security evaluation; security metrics; cybersecurity digital library